A Case of Concurrent Molybdenosis, Secondary Copper, Cobalt and Selenium Deficiency in a Small Sheep Herd in Northern Germany - Helmer, Carina (Animals (Basel), 2021)
SIMPLE SUMMARY: Mineral deficiencies are very widespread among small ruminant herds throughout the world and play a big role in small ruminant herd health management. This paper describes the occurrence of a primary molybdenosis causing secondary copper deficiency, combined with ovine white liver disease (cobalt deficiency) and white muscle disease (selenium deficiency) in a group of pastured ram lambs in Northern Germany. To the authors’ knowledge, this is the first proven report of multiple trace element deficiencies in sheep in Germany for decades. ABSTRACT: To the author’s knowledge this paper describes the first proven report of a combined primary molybdenosis, secondary copper (Cu) deficiency, Ovine White Liver Disease—Cobalt (Co) deficiency, and selenium (Se) deficiency in a small pedigree herd of White Horned Heath sheep in Germany (8 ewes, 2 rams, 3 yearling ewes, 17 lambs) for decades. Clinical signs associated with these mineral deficiencies in a group of pastured ram lambs included emaciation, conjunctivitis, anaemia, growth retardation, discolouration of the wool and photodermatitis. Morbidities and mortalities arose in 4–6-month-old lambs despite intensive veterinary treatment in the summer of 2014 and 2015 (n = 13, 23% died). Se (3/5), Cu (4/7), and Co (3/3) deficiencies in combination with elevated values for Molybdenum (Mo, 2/2) were found. Hamburg is a large industrial city and an input of heavy metals from surrounding industries and coal-fired power stations in combination with a sandy, non-fertilised soil and monoculture grass species might offer a potential explanation for the severity of mineral deficiencies observed in this herd.